The Prevention of Anemia on Pregnant Women through Counseling and The Administration of Fe Tablet in Jatinom, Kec. Kanigoro, Kab Blitar - Ulfa, Maria; Monica, Laily Prima; Wibisono, Wahyu (STIKes Patria Husada Blitar, 2020)
In Indonesia, the anemia prevention program for pregnant women is done by providing iron supplements as many as 90 tablets during pregnancy. However, many pregnant women refuse or do not comply with this recommendation for various reasons. The compliance of taking Fe tablets is less than 90% of iron tablets that should be taken. The compliance of pregnant women to take iron tablet is an important factor in ensuring an increase of hemoglobin levels of pregnant women. The right information and right method related to anemia become very important for the community and become very important in order to reduce the risk of maternal death. The purpose of this community service was to increase the knowledge of pregnant women about anemia, the impact of anemia, and the importance of fe tablets. The method was in the form of counseling and giving Fe tablets to pregnant women classes in Jatinom, Kec. Kanigoro, Kabupaten Blitar. The result showed the knowledge and compliance of pregnant women in consuming Fe tablets were 5 participants (25%) in good category, 10 participants (50%) in fair category, 5 participants (25%) in lack category. After the counseling process, there was an increase in the knowledge and compliant to take the Fe tablet. There were15 participants (75%) in good category and 5 participants (25%) in moderate category